(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper is an RTOS based architecture designed for the purpose of data transmission between two controlling units through IWSN without collision. RTOS is a Process which will be done between hardware and application. Here, stack is the one which is used to avoid the independency of the layers from one with another inside the protocol comes under the standard IEEE802.15.4.Stack having two techniques (PAL and NILI) we are using in the IEEE 802.15.4 to reduce the collision and timing. Mostly, during the packets transmission some collision may occur. This collision has to be avoided to prevent the data loss during the transmission. The project deals with the data transmission between two units in the exact time without any collision. The data transmission time is increased with the protocol standard. One of the section runs with RTOS and LPC2148 as master node and another as normal data acquisition node to which sensors are connected. Data acquisition node uses the Peripheral Interface controller. Communications between two nodes (hardware and application) are accomplished through IEEE 802.15.4.